2020
DOI: 10.1016/j.jcot.2020.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Successful two-stage primary total knee arthroplasty for infective arthritis of the knee – our experience

Abstract: Background: The incidence of septic arthritis is 2e10/100,000. Morbidity is higher with persistent joint dysfunction in up to 30%. Osteoarthritic knee with infection presents a rare challenge, with no established approach for treatment exists. We present our experience of managing infected degenerative joint disease (DJD) with two-stage primary arthroplasty similar to the management of periprosthetic joint infection. Patients and methods: Four patients presented to us between 2016 and 2018 with advanced DJD as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…While the literature has primarily focused on developing treatment modalities to improve the outcomes of TKA following native knee septic arthritis, the contemporary literature has yet to define the magnitude of risk that prior septic arthritis infections have on the outcome of TKA. Most studies, limited by sample size or lack of a control cohort, have suggested that the incidence of PJI following total joint arthroplasty is somewhere between 3% and 15% in patients with prior native joint septic arthritis, whereas the overall rate of PJI after TKA in U.S. hospital registries is approximately 1% 1,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the literature has primarily focused on developing treatment modalities to improve the outcomes of TKA following native knee septic arthritis, the contemporary literature has yet to define the magnitude of risk that prior septic arthritis infections have on the outcome of TKA. Most studies, limited by sample size or lack of a control cohort, have suggested that the incidence of PJI following total joint arthroplasty is somewhere between 3% and 15% in patients with prior native joint septic arthritis, whereas the overall rate of PJI after TKA in U.S. hospital registries is approximately 1% 1,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…1), in some cases necessitating total knee arthroplasty (TKA) 3,4 .Previously reported rates of periprosthetic joint infection (PJI) after TKA in patients with previous septic arthritis of the native knee have ranged from 3% to 15%, whereas the overall rate of PJI following TKA is approximately 1% [5][6][7][8] . Most reports on septic arthritis of the native knee preceding TKA have been limited by small cohorts, have been systematic review-type articles, and/or have lacked reporting of survivorship compared with a control cohort 1,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . Therefore, we sought to compare the outcomes of TKA in patients with a history of native knee septic arthritis and those in a matched control cohort of patients with primary osteoarthritis (OA) during the same time period.The primary purpose of the present study was to compare the outcomes of TKA in patients with a history of native knee septic arthritis (with a specific focus on survivorship free of any infection, PJI, aseptic revision, any revision, and any reoperation) with those in a matched cohort of patients with Disclosure: The Disclosure of Potential Conflicts of Interest forms are provided with the online version of the article (http://links.lww.com/JBJS/G605).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies were mostly case reports 3,[11][12][13] , and evidences regarding the therapy aspect was limited.…”
Section: Introductionmentioning
confidence: 99%